(untitled) (Indian Journal of Veterinary Pathology, 2025)
In order to identify the cause of death, a carcass of an 8-month-old Soviet chinchilla was presented to Department of Veterinary Pathology, GADVASU, Ludhiana with the history of emaciation and dermatitis. A detailed investigation of the carcass revealed crusty lesions in ears and alopecic patches around eyes and lips. The parasitological investigation of skin scrapings revealed the presence of Notoedres cati, which very rarely infests rabbits. Histopathology revealed multiple mite burrows in skin along with hyperkeratosis and lymphoeosinophilic infiltration. Based on the gross lesions, morphology and histopathology, a very rare case of Notoedric mange in soviet chinchilla is documented.